2022
DOI: 10.1186/s13018-022-03443-4
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 inhibits nucleus pulposus cell apoptosis, inflammation and extracellular matrix degradation via the YAP1/TAZ pathway in rats with intervertebral disc degeneration

Abstract: Purpose Intervertebral disc degeneration (IDD) is one of the main causes of low back pain, which not only affects patients’ life quality, but also places a great burden on the public health system. Recently, ginsenoside Rg1 has been found to act in IDD; however, the mechanism is still unclear. The purpose of this study is to explore the function of ginsenoside Rg1 and its molecular mechanism in IDD. Methods The rat model of IDD and nucleus pulposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…And Yang et al . ( 2022 ) also demonstrated that ginsenoside Rg1 had a significant inhibitory effect on the secretion level of inflammatory factors, redox activity, ECM degradation, and cell apoptosis in NP cells. However, the mechanism of ginsenoside Rg1 to alleviate the IVDD progression was far to be clear and comprehension.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…And Yang et al . ( 2022 ) also demonstrated that ginsenoside Rg1 had a significant inhibitory effect on the secretion level of inflammatory factors, redox activity, ECM degradation, and cell apoptosis in NP cells. However, the mechanism of ginsenoside Rg1 to alleviate the IVDD progression was far to be clear and comprehension.…”
Section: Discussionmentioning
confidence: 93%
“…In the present study, ginsenoside Rg1 could promote cell proliferation and inhibit the apoptosis, inflammation response, and ECM degradation in IL-1β-induced rat NP cells, consistent with the results of Yang et al . ( 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation